Sensible Reason in Argumentation: Beyond the Emotion/Reason Divide - Morales Vidales , Amanda Panambi (Człowiek i Społeczeństwo, 2026)
This article introduces the concept of sensible reason in order to explain a dimension of argumentation that is often treated too broadly under the category of emotion. The central claim is that certain affective, perceptual, symbolic, and situated elements do more than accompany arguments as persuasive intensifiers: they function within argumentation as part of what gives claims meaning, force, orientation, and justification. For that reason, the term sensible reason is proposed as a more precise way of accounting for how the sensible operates within argumentative practice. The article clarifies what this concept means by arguing that sensible reason is not reducible to explicit emotion-language, propositional form, or rhetorical ornament, but must be understood through its symbolic expression, its cultural and collective constitution, its situational character, and its role in the production of argumentative intelligibility. From this perspective, argumentation appears not simply as an inferential structure, but as a social and situated practice in which sensible forms participate in what arguments do. The case of the Zapatista Army of National Liberation (Ejército Zapatista de Liberación Nacional, EZLN) and its political formulation of digna rabia (“dignified rage”) is used to show how a sensible reason may become historically mediated, multimodal, collective, and publicly operative within political argumentation.